Comments:LaTeX-code for the most common formulas

From GeoGebra Manual
Revision as of 02:03, 6 October 2011 by Acron (talk | contribs) (→‎Formulas)
Jump to: navigation, search

If you have somewhere a very long formula, please share it with us. This will save time for everybody!

Design-Tip

  • A space before the formula leads to the box around the line.
  • Don't hesitate it is not looking so good. That can be done by anybody else.
  • An easy solution to get the same look is to copy the lines of an other formula for you formula.

How to use the formulas

Just copy the text in the dotted box into you text-input-box. If the formula should be dynamic you need to insert the object at the place of the variable that is used here.

Formulas

==Useful Formulas==
Usage LaTex Input LaTex Output
Slope for a straight line m=\frac{y_2-y_1}{x_2-x_1} m=\frac{y_2-y_1}{x_2-x_1}
Compound Interest Amount = Principal * \left( 1 + \frac {rate}{periods} \right) ^ {time\; *\; periods} Amount = Principal * \left( 1 + \frac {rate}{periods} \right) ^ {time\; *\; periods}
Slope for a straight line m=\frac{y_2-y_1}{x_2-x_1} m=\frac{y_2-y_1}{x_2-x_1}
Quadratic Equation a x^2\; +\; b x\; +\; c\; =\; 0 a x^2\; +\; b x\; +\; c\; =\; 0
Vertex Form f(x)\; =\; a(x\; -\; h)^2\; +\; k f(x)\; =\; a(x\; -\; h)^2\; +\; k
Factored Form f(x)\; =\; (x\; +\; a)\;(x\; +\; b) f(x)\; =\; (x\; +\; a)\;(x\; +\; b)
Quadratic Formula x\; =\; \frac {-b\; \pm\; \sqrt {b^2\; -\; 4ac}}{2a} x\; =\; \frac {-b\; \pm\; \sqrt {b^2\; -\; 4ac}}{2a}
Cubic Equation a x^3\; +\; b x^2\; +\; c x\; +\; d\; =\; 0 a x^3\; +\; b x^2\; +\; c x\; +\; d\; =\; 0
Cubic Vertex Form a x^3\; +\; b x^2\; +\; c x\; +\; d\; =\; 0 a x^3\; +\; b x^2\; +\; c x\; +\; d\; =\; 0
Basic Trigonometry Forms sin A = \frac {opp}{hyp} = \frac {a}{c} = (a/c) sin A = \frac {opp}{hyp} = \frac {a}{c} = (a/c)
f(x)\; =\; a\; sin\; b\;(x\; -\; h)\; +\; k f(x)\; =\; a\; sin\; b\;(x\; -\; h)\; +\; k
f(x)\; =\; a\; sin\; (B x + C) + k f(x)\; =\; a\; sin\; (B x + C) + k
b\;(x\; -\; h)\; = B\; \left( x\; -\; \frac {-C}{B} \right) b\;(x\; -\; h)\; = B\; \left( x\; -\; \frac {-C}{B} \right)
h\; = \frac {-C}{B} h\; = \frac {-C}{B}
Limit forms \lim\limits_{\substack{x \to ? \\x > ?} } \lim\limits_{\substack{x \to ? \\x > ?} }
\lim\limits_{\substack{x \to ? \\x < ?} } \lim\limits_{\substack{x \to ? \\x < ?} }
\lim\limits_{x \to \infty} \lim\limits_{x \to \infty}
© 2022 International GeoGebra Institute